Penegakan Hukum Pidana Lingkungan di Indonesia - Mubarok, Mafi' (Al-Jinayah : Jurnal Hukum Pidana Islam, 2019)
The definition of environmental crime is to pollute and damage the environment, as stipulated in 98-115 UUPPLH. In UUPPLH there are two principles in the use of criminal law facilities, namely as ulmitimum remedium and remedium premium. Whereas in its formulation, there are formal criminal and material criminal acts, even formal and material ones, namely Article 98 paragraph (2), (3) and article 99 paragraph (2), (3) UUPPLH. Criminal Law Subjects in UUPPLH are individuals, legal entities and environmental officials. Enforcement of criminal law in the field of environment in Indonesia is currently not in line with community expectations. Judging from the legal structure, because (1) judicial products are not sensitive to environmental crisis and sense of justice, (2) weakness in terms of law enforcement infrastructure, (3) environmental officials who commit environmental crimes in various forms, and (4) failure of government bureaucracy because it is insensitive to ecological premises. As for the substance of the law, because horizontally there are many policies that overlap and do not take sides with the interests of the environment, both in formulation and in its application. For legal culture, because (1) there are perceptions from law enforcement officials that environmental cases are ordinary cases, (2) still poor legal culture, (3) lack of socialization to the public regarding environmental law, and (4) economic downturn